Changes in femur stress after hip resurfacing arthroplasty: response to physiological loads. - Little, J; Taddei, F; Taddei, F; Viceconti, M; Viceconti, M; Murray, D; Murray, D; Gill, H; Gill, H (2007)
BACKGROUND: Hip resurfacing arthroplasty is being increasingly considered as an alternative to total hip arthroplasty in young, active patients. Hip resurfacing arthroplasty is reported to preserve the normal joint mechanics. However, there is concern, in the short term, due to frequent occurrence of femoral neck fractures. METHODS: We evaluated changes in femoral mechanics after hip resurfacing arthroplasty. We used an experimentally validated, distributed material finite element model of a cadaveric femur before and after hip resurfacing arthroplasty. Bone stiffness and strength values representing normal, elderly and osteoporotic bone were used. For a physiological load case, bone strains were compared with literature values for total hip arthroplasty and a risk of fracture scalar calculated. FINDINGS: The changes in peak stresses after hip resurfacing arthroplasty were low in relation to the failure strength of bone and the fracture risk was low. The intact and implanted finite element models showed bone strains after hip resurfacing arthroplasty were closer to the intact condition than after total hip arthroplasty. INTERPRETATION: The bone stresses predicted after resurfacing in both the normal and aged femoral neck were not sufficient to be a potential cause of fracture.